A beleza da margem, à margem da beleza: a construção do espaço público em Belo Horizonte - Jesus, Cláudio Roberto de (Programa de Pós-Graduação de Geografia Humana e Programa de Pós-Graduação de Geografia Física, 2014)
The intention of this paper is rereading the history of Belo Horizonte, from the Leis de Posturas established until the 50’s, emphasizing those that deal with regu- lation of the activity of ambulant. The analysis will focus on the discussion about the contradictions between public and private space, memory in relation to the city, social practices, leisure, social networks and clash with government. The discussion will depart from the more general formulations, emphasizing, however, the Brazilian reality. In this sense, the history of Belo Horizonte proves to be ex- tremely rich in examples of socio-spatial contradictions. Since the first years of its creation, the capital city of Minas Gerais has been producing a space marked by the action of the State, not only because of the rigidity of the original project, but also because of the recurrent attempts to regulate the social practices by the Leis de Posturas. These laws are reflections of socio-spatial conflicts of which epoch and will impact the daily lives of individuals.